Pengembangan Sistem Administrasi Berbasis Web di Asrama Ekasari menggunakan Metode Agile - Zahra, Nur Rahma Ditta; Nugraha, Nur Iman; Azzahra, Kanaya Sabila; Widhiwipati, David Reza; Mindara, Gema Parasti; Wicaksono, Aditya (Jurnal ICT: Information Communication & Technology, 2025)
This study develops the SADE application (Sistem Administrasi Asrama Digital Ekasari) Digital Dormitory Administration System Ekasari using the Agile method to improve the administration of Asrama Ekasari at IPB University. Manual management has caused delays, inaccuracies, and limited information access. The web-based system enables real-time management of resident data, finances, and activities, featuring financial visualization through line charts as a simple business intelligence tool to assist decision-making. The system is built using React.js for the frontend, Express.js for the backend, and MySQL as the database. Black-box testing ensures all functions operate according to specifications. User evaluations indicate that most features work well, although the mobile interface requires improved responsiveness. Overall, SADE supports digital transformation in dormitory administration while enhancing communication between residents and management.